Schools and public health : past, present, future - Gard, Michael, 1965-; Pluim, Carolyn (Critical education policy and politics., 2014)
"Schools and Public Health is a meditation on the past, present, and future of the relationship between public health and American public schools. Gard and Pluim begin by developing a historical account of the way schools have been used in the public health policy arena in America. They then look in detail at more contemporary examples of school-based public health policies and initiatives in order to come to a judgment about whether and to what extent it makes sense to use schools in this way. With this as the foundation, the book then offers answers to the question of why schools have so readily been drawn into public health policy formulations. First, seeing schools as a kind of 'miracle factory' is a long standing habit of mind that discourages careful consideration of alternative public health strategies. Second, schools have been implicated in public health policy in strategic ways by actors often with unstated political, cultural, ideological, and financial motivations. Finally, the authors call for a more sophisticated approach to public health policy in schools and suggest some criteria for judging the potential efficacy of school-based interventions. In short, the potential effectiveness of proposed interventions needs to be assessed not only against existing historical evidence, but also against the competing roles society expects schools to play and the working-life realities for those charged with implementing public health policies in schools."--